STUDY REGARDING THE VALUE OF THE PLAYERS ANTHROPOMETRIC INDICATORS MEMBERS OF THE ELITE EUROPEAN HANDBALL TEAMS QUALIFIED AT THE FINAL TOURNAMENTS - SANDOR, Iosif; NEAG, Simina-Aurelia (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2021)
Introduction. Handball players who manage to perform at the highest level have certain specific qualities. Through the results obtained in all world competitions, European national teams are considered the best teams in the world. Aim. The aim is to determine the current trend about the value of anthropometric indicators, primarily the body mass index, and its role in achieving performance. Materials and methods. The data of anthropometric parameters (age, height, weight, and body mass index - BMI) from 966 handball players who participated in 2016, 2018, and 2020 editions of the European Men's Handball Championship had been analyzed. Next, the finalist and non-finalist teams' BMI was analyzed, and then its evolution according to playing position. Results. The analysis shows that in the last three editions of the European Championship, an approximately constant value of the studied indicators is kept. The differences between the editions are not statistically significant. The average age is 27 years, the average weight is about 94 kg, the average height is 1.92 cm, and the BMI is 25. The body mass index did not register statistically significant differences for the same playing position in the last three editions analyzed. Conclusions. The data obtained from the study show what the current values of the leading anthropometric indicators of elite European handball players are. These indicators do not play an essential role in ranking in the first positions of the final tournament. REZUMAT. Studiu privind valoarea indicatorilor antropometrici ai jucătorilor de elită membri ai echipelor europene de handbal calificate la turneele finale. Introducere. Jucătorii de handbal care reușesc să performeze la cel mai înalt nivel au anumite calități specifice. Echipele naționale europene, prin rezultatele obținute la toate competițiile mondiale, sunt considerate cele mai performante echipe. Scop. Scopul este de a determina tendința actuală în ceea ce privește valoarea indicatorilor antropometrici, în special indicele de masă corporală și rolul său în atingerea performanțelor. Materiale și metode. Au fost analizate datele parametrilor antropometrici (vârstă, înălțime, greutate și indicele de masă corporală - IMC) de la 966 de jucători de handbal care au participat la edițiile 2016, 2018 și 2020 ale Campionatului European de handbal masculin. Apoi a fost analizat IMC-ul echipelor finaliste și non-finaliste și evoluția acestuia în funcție de posturile de joc. Rezultate. Analiza arată că la ultimele trei ediții ale Campionatului European se păstrează o valoare aproximativ constantă a indicatorilor studiați. Diferențele dintre ediții nu sunt semnificative din punct de vedere statistic. Vârsta medie este de 27 de ani, media greutății este de 94 kg, înălțimea medie 1,92 cm, iar IMC-ul este 25. Indicele de masă corporală nu a înregistrat diferențe statistic semnificative pentru același post de joc la cele trei ediții analizate. Concluzii. Datele obținute din studiu arată care sunt valorile actuale ale principalilor indicatori antropometrici ai handbaliștilor europeni. Acești indicatori nu joacă un rol decisiv în clasarea echipelor în primele poziții ale unui turneu final. Cuvinte cheie: jucători de elită, indicatori antropometrici, indicele de masă corporală-IMC, Campionat European.